Decreased mortality in patients with isolated severe blunt traumatic brain injury receiving higher plasma to packed red blood cells transfusion ratios. Issue 1 (January 2018) - Haltmeier, Tobias; Benjamin, Elizabeth; Gruen, John Peter; Shulman, Ira A.; Lam, Lydia; Inaba, Kenji; Demetriades, Demetrios
Abstract: Introduction: Higher transfusion ratios of plasma to packed red blood cells (PRBC) and platelets (PLT) to PRBC have been shown to be associated with decreased mortality in major trauma patients. However, little is known about the effect of transfusion ratios on mortality in patients with isolated severe traumatic brain injury (TBI). The aim of this study was to investigate the effect of transfusion ratios on mortality in patients with isolated severe blunt TBI. We hypothesized that higher transfusion ratios of plasma to PRBC and PLT to PRBC are associated with a lower mortality rate in these patients. Methods: Retrospective observational study. Patients with isolated severe blunt TBI (AIS head ≥ 3, AIS extracranial < 3) admitted to an urban level I trauma centre were included. Clinical data were extracted from the institution's trauma registry, blood transfusion data from the blood bank database. The effect of higher transfusion ratios on in-hospital mortality was analysed using univariate and multivariable regression analysis. Results: A total of 385 patients were included. Median age was 32 years (IQR 2–50), 71.4% were male, and 76.6% had an ISS ≥ 16. Plasma:PRBC transfusion ratios ≥ 1 were identified as an independent predictor for decreased in-hospital mortality (adjusted OR 0.43 [CI 0.22–0.81]). PLT:PRBC transfusion ratios ≥ 1 were not significantly associated with mortality (adjusted OR 0.39 [CI 0.08–1.92]). Conclusion: This study revealed plasma to PRBC transfusion ratios ≥ 1 as an independent predictor for decreased in-hospital mortality in patients with isolated severe blunt TBI.